2021
DOI: 10.1177/2156759x20981034
|View full text |Cite
|
Sign up to set email alerts
|

School or Guidance Counselor: How the Title Influences Public Perception

Abstract: School counselors are one of the few professions that remain split on their professional title. We replicated a previous study to determine whether the results of the original study measuring the impact of language on perceptions of school counselors’ competency were replicable by surveying a sample of the general population. Participants who completed the surveys with the term “guidance counselor” were statistically less likely to believe that school counselors were able to perform the 25 tasks assessed on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Effectively meeting student needs requires that counselors advocate for their roles. Advocating includes educating principals, educators, and community members about their titles (Baker et al, 2021;Zyromski et al, 2018), participating in professional development, and dedicating themselves to providing more student-centered services versus school-centered (Blake, 2020;Lambie et al, 2019;Savitz-Romer et al, 2021;Wilder, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectively meeting student needs requires that counselors advocate for their roles. Advocating includes educating principals, educators, and community members about their titles (Baker et al, 2021;Zyromski et al, 2018), participating in professional development, and dedicating themselves to providing more student-centered services versus school-centered (Blake, 2020;Lambie et al, 2019;Savitz-Romer et al, 2021;Wilder, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the school counseling profession has struggled to define its roles and responsibilities (Cinotti, 2014; DeKruyf et al., 2013). Variations across states, districts, and among school leaders in how school counselors' work is defined, how they are supported and supervised (Randick et al., 2018), as well as their job titles (Baker et al., 2021; Zyromski et al., 2018), illustrate the inconsistency in utilizing school counselors to support student outcomes (Blake, 2020). The ASCA National Model (2019) recommends that school counselors spend 80% of their time delivering direct and indirect services.…”
Section: Introductionmentioning
confidence: 99%
“…While research has shown that school leaders and administrators have misconceptions about the work of counselors (e.g., Lewis et al, 2020), there is evidence that this confusion is also prevalent among the general public. This was clear from recent work by Baker et al (2021) which found that the public perceives the titles "school counselor" and "guidance counselor" differently; specifically, the public rated "school counselors" as more competent despite these titles being used synonymously in the counseling profession. In recent years, ASCA (2019d) and others have advocated for using the term "school counselor" in lieu of "guidance counselor" as they believe it more accurately reflects the role of today's counselors who, as educators, advocates, and leaders, do much more than provide course and career advice.…”
Section: Role Confusionmentioning
confidence: 99%
“…In recent years, ASCA (2019d) and others have advocated for using the term "school counselor" in lieu of "guidance counselor" as they believe it more accurately reflects the role of today's counselors who, as educators, advocates, and leaders, do much more than provide course and career advice. Baker et al (2021) showed, however, that the general public is not aware of these updated roles. This confusion is deleterious given that it can affect how parents and guardians perceive counselors' credibility and competence, and consequently, their likelihood of seeking out school counseling services for their children.…”
Section: Role Confusionmentioning
confidence: 99%
“…Their professional responsibilities range from individual counseling, group counseling, and classroom lessons to family outreach and college and career readiness counseling (ASCA, n.d.). However, despite national standards, a professional model, and guidance on appropriate roles, these professionals face varying expectations of their role and responsibilities from students, parents, school principals, teachers, and even counselors themselves (Baker et al, 2021; Lewis et al, 2020; Zyromski et al, 2018). This is partially due to the fact that roles are context bound, meaning an individual’s understanding of the expectations for their role is influenced by organizational features in their environment.…”
Section: Role Theory and School Counselorsmentioning
confidence: 99%